2014
DOI: 10.18632/oncotarget.2405
|View full text |Cite
|
Sign up to set email alerts
|

IsomiR expression profiles in human lymphoblastoid cell lines exhibit population and gender dependencies

Abstract: For many years it was believed that each mature microRNA (miRNA) existed as a single entity with fixed endpoints and a ‘static’ and unchangeable primary sequence. However, recent evidence suggests that mature miRNAs are more ‘dynamic’ and that each miRNA precursor arm gives rise to multiple isoforms, the isomiRs. Here we report on our identification of numerous and abundant isomiRs in the lymphoblastoid cell lines (LCLs) of 452 men and women from five different population groups. Unexpectedly, we find that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
142
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(165 citation statements)
references
References 32 publications
23
142
0
Order By: Relevance
“…Small RNA sequencing studies in multiple species have yielded an increasingly detailed understanding of the miRNA repertoire (Ruby et al 2006(Ruby et al , 2007Landgraf et al 2007;Morin et al 2008;Chiang et al 2010;Berezikov et al 2011;Cloonan et al 2011;Loher et al 2014;Xia and Zhang 2014). These studies have shown that miRNA 3 ′ -ends are generated with low stringency resulting in the frequent coexpression of 3 ′ -variants.…”
Section: Introductionmentioning
confidence: 99%
“…Small RNA sequencing studies in multiple species have yielded an increasingly detailed understanding of the miRNA repertoire (Ruby et al 2006(Ruby et al , 2007Landgraf et al 2007;Morin et al 2008;Chiang et al 2010;Berezikov et al 2011;Cloonan et al 2011;Loher et al 2014;Xia and Zhang 2014). These studies have shown that miRNA 3 ′ -ends are generated with low stringency resulting in the frequent coexpression of 3 ′ -variants.…”
Section: Introductionmentioning
confidence: 99%
“…performed a systematic molecular-level analysis (mainly including mRNA, DNA methylation, microRNA (miRNA) and protein expression levels), and suggested to develop sex-specific therapeutic strategies in certain cancer types1. Recent studies suggest that proteomes may differ between males and females23, and sex differences may exist in mRNA4, miRNA expression567 and isomiR (miRNA variants) expression levels89. For example, AT2R can influence vascular responses with sexually dimorphic10, and some genes are influenced by androgens or estrogen1112.…”
mentioning
confidence: 99%
“…Advanced research from NGS (next-generation sequencing) suggests isomiRs are multiple distinct mature miRNAs that arise from the same hairpin arm and 5' or 3' ends of their sequences and are different from canonical miRNAs in public databases such as miRBase (9). Moreover, recent studies have shown variation in cleavage site for DROSHA and DICER1 enzymes or even other miRNAs processing enzymes or posttranscriptional editing which lead to sequence modification in miRNAs (1) that are classified as "trimming variants" (10).…”
Section: Isomir Originmentioning
confidence: 99%
“…For example, the human miR-451 gene cleavages by Argonaut 2 (AGO2) to generate a molecule-intermediate called as 'ac-pre-miRNA' that are processed to mature miRNAs by exonucleolytic trimming (3). Data received from lymphoblastoid cell lines and analysis of Argonaute verify connection of many isomiRs with the Argonaute silencing complex and their important role in RNA interference pathway (9). There are three main types of isomiRs including 3′ isomiRs, 5' isomiRs and internal modifications (1) so called polymorphic isomiRs and 3′, 5' miR variants subclassified to 'templated' and 'non-templated' modification (figure 1).…”
Section: Isomir Originmentioning
confidence: 99%
See 1 more Smart Citation